1977
DOI: 10.1111/j.1559-1816.1977.tb00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Motivating People to be Physically Active: Self‐Persuasion vs. Balanced Decision Making1

Abstract: Female members of an adult physical fitness club, who had been inactive for a period of at least one month, were assigned to one of four treatment groups. A control group received no treatment while the other three groups underwent different treatments during a telephone interview. A regular call‐up group received a standard club telephone interview advocating greater participation in the club's activities; a decision‐balance‐sheet group completed a list of anticipated gains and losses for attending the club's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 10 publications
1
32
0
Order By: Relevance
“…The authors suggested the process of self‐persuasion, whereby a person becomes aware of more positive incentives that outweigh the negative incentives for carrying out a given course of action (in this case, attending the exercise class), was likely to have accounted for the positive effect seen in the relevant decisional balance group (Hoyt & Janis 1975). Similar findings were reported by Wankel and Thompson (1977) in a study designed to motivate attendance of inactive members of a physical fitness club and Colten and Janis (1982), who studied the effects of completing, or not completing, a decisional balance which explored the pros and cons of going versus not going on a recommended 1 200‐calorie diet.…”
Section: Decisional Balancesupporting
confidence: 74%
“…The authors suggested the process of self‐persuasion, whereby a person becomes aware of more positive incentives that outweigh the negative incentives for carrying out a given course of action (in this case, attending the exercise class), was likely to have accounted for the positive effect seen in the relevant decisional balance group (Hoyt & Janis 1975). Similar findings were reported by Wankel and Thompson (1977) in a study designed to motivate attendance of inactive members of a physical fitness club and Colten and Janis (1982), who studied the effects of completing, or not completing, a decisional balance which explored the pros and cons of going versus not going on a recommended 1 200‐calorie diet.…”
Section: Decisional Balancesupporting
confidence: 74%
“…The procedure was similar to that used in the Wankel and Thompson (1977) study. Respondents were asked to think of and record the anticipated gains and losses, which may arise from their exercising two more sessions per week.…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…The DBS has been shown on several occasions to be effective in improving exercise participation and adherence (e.g. Hoyt & Janis, 1975;Wankel & Thompson, 1977;Wankel et al, 1985). Therefore comparing the comparative success of the DBS against implementation intentions alone or used in conjunction with the DBS, would represent a more stringent test of the efficacy of implementation intentions.…”
Section: Introductionmentioning
confidence: 99%
“…Theabsenceof a relationship betweeninternalhealthlocusof control and supervised running is less remarkable because small supervised exercise programs permit effective interventions employing more client-centered approaches using behavior modification and cognitive-behavior modification techniques. Several effective exercise interventions in supervisedsettingshavebeen basedin parton decisiontheories that includeroles for perceivedbehavioral control,outcomeexpectancy values,andperceivedbarriersforactivity (Belisle, Roskies, & Levesque, 1987;Hoyt & Janis, 1975;King & Frederiksen, 1984;Marlatt & Gordon, 1985;Martin et al, 1984;Wankel & Thompson, 1977;Wankel, Yardley, & Graham, 1985).…”
Section: Discussionmentioning
confidence: 97%